Estimated Financial Distress in Manufacturing Companies Listed on the Indonesian Stock Exchange - Julyazti, Nadya Fritanita; Maulana, Marcel (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the possibility of financial distress in several manufacturing companies listed on the Indonesia Stock Exchange. This research uses 3 manufacturing companies. The data used was from 2018 to 2020. The analysis technique used to predict the tendency of financial distress is the Alant's Z-score. According to the analysis that has been carried out, it was found Based on the results of Almant's Z-score analysis, it was found that PT Asiaplas Industries (APLI) had different conditions from 2018 to 2020. In 2018 APLI is predicted to experience financial distress, in 2019 APLI is in a gray area position, while in 2010 APLI shows better conditions, because they are able to escape from bankruptcy symptoms, A different thing happened to SIPD in 2018 and 2019 which was predicted to be far from bankruptcy, but in 2020 SIPD experienced a decline in financial performance and is predicted to experience bankruptcy in the near future. The same thing happened to LPIN, in 2018 the company was predicted to escape bankruptcy, but in 2019 and 2020 LPIN actually experienced a decline in the company's performance and was predicted to experience financial distress in the coming years. Kata Kunci: Financial Distress, Z-score Almant, Working Capital to Assets, Retaining Earning to Assets, Earning Before Interest and Tax to Total Assets, & Market Value of Equity to Book Value of Debt